IMPROVING STUDENTS NARRATIVE WRITING PROCESS THROUGH SERIES OF PICTURE CLASSROOM ACTION RESEARCH - Cahyani, Yani; Nurjanah, Dede Mita (PROJECT (Professional Journal of English Education), 2019)
Dealing with the difficulties in writing can be carried out by implementing strategies in teaching writing. This research is done to know the benefits of using series of pictures in the process of narrative writing. It is expected that the research can be interesting and enjoyable ways. It is also expected by  the teacher to know  that using series of picture, the students can be stimulated to think cratively in gaining the ideas and learning the narrative writing well. The method of the research was quantitative method, or more specifically quasi-experimental design to see the effectiveness series of picture toward students ’writing skill in narrative text. The population of  this reserach was twelfth grade students of SMK Negeri 1 Cijati Cianjur and the sample was class XII. The form of instrument in this research was narrative text writing test. The data was collected by using pre-test and post-test measurement on the control and experiment class and comparing the gained scores between both classes. The result presented that the picture series as media in writing narrative text is effective towards students’writing skill in narrative text. The result of calculation presented that in the significance degree of 5%,the value of t-test (to) >t-table (tt) (5.514> 1.992).According to the criteria of the test, the result showed that there is a significant diferrence between students’writing skill in narrative text by using picture series as media and without picture series.it means that, the picture series is effective and applicable as the media in writing narrative text.